Coupling a power system model with a hydrological model improves the representation of sub-monthly hydropower flexibility - Baratgin, Laure; Quirion, Philippe; Polcher, Jan; Dumas, Patrice (Applied energy, 2025)
Integrating large amounts of variable renewable power generation increases the need for flexible resources in the power system. Hydropower can be a precious asset for managing the variability in the grid. However, it will be subject to evolving constraints related to changes in the water resources and the operation of multi-purpose reservoirs. This study explores the value of coupling a power system model with a hydrological model that represents the operation of hydroelectric dams, to simulate an hourly hydropower schedule consistent with a realistic management of the hydropower reservoirs at the national grid level. We model the French power system with the optimization model EOLES-Dispatch and assess the impact of the coupling with the ORCHIDEE model, which represents hydropower management. We find that this new method allows us to simulate a hydropower schedule closer to the observed production, while power system models tend to overestimate the flexibility of hydropower. Considering a prospective 2050 power mix, we also find that accounting for these additional constraints leads to more frequent unsatisfied demand, which is underestimated by the usual representation of hydropower. Such a coupling of hydrological and power system modeling paves the way for a more robust representation of power dispatch in future power mixes, taking into account the joint evolution of water resources and power systems. •Hydropower flexibility is overestimated in most power system models.•A new integrated framework combining power system and hydrological modeling.•This coupling improves the simulation of historical hydropower generation in France.•Matters when assessing the power supply security of future power systems.